2023
DOI: 10.1007/s13201-023-01937-y
|View full text |Cite
|
Sign up to set email alerts
|

Water disinfection using durable ceramic filter coated with silver nanoparticles synthesized using actinomycetes

Karam Rabee Wafy,
Eslam Ibrahim El-Aswar,
Walaa Salah El-din Mohamed
et al.

Abstract: Contamination with pathogens degrades water quality and is a major cause of many waterborne diseases. The aim of this research is to reduce the global disease burden by presenting an efficient, durable, and low-cost ceramic filter impregnated with actinomycetes-mediated silver nanoparticles (AgNPs) for water disinfection in rural areas. This marks the first report on the simultaneous biosynthesis of AgNPs utilizing cell-free supernatants obtained from terrestrial actinomycetes. An easy and efficient method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…However, in the case of CPWF with Eragrostis tef husk, some residues may persist despite the combustion process . The research findings, comparing combustible materials such as sawdust, maize cob, and cassava, revealed that sawdust produced the most optimal porosity . As a result, they achieved the highest flow rate of filtered water.…”
Section: Cwf Preparation Methodsmentioning
confidence: 90%
See 4 more Smart Citations
“…However, in the case of CPWF with Eragrostis tef husk, some residues may persist despite the combustion process . The research findings, comparing combustible materials such as sawdust, maize cob, and cassava, revealed that sawdust produced the most optimal porosity . As a result, they achieved the highest flow rate of filtered water.…”
Section: Cwf Preparation Methodsmentioning
confidence: 90%
“… 45 The research findings, comparing combustible materials such as sawdust, maize cob, and cassava, revealed that sawdust produced the most optimal porosity. 49 As a result, they achieved the highest flow rate of filtered water. The high porosity of the filter plays a crucial role, as it allows water to pass through easily while efficiently removing impurities.…”
Section: Cwf Preparation Methodsmentioning
confidence: 97%
See 3 more Smart Citations